Total synthesis of proposed auranthine - Kshirsagar, Umesh A.; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2010)
Starting from CBz-protected glutamic anhydride and Boc-protected o-aminobenzyl amine, the first total synthesis of proposed structure of auranthine has been reported. An intramolecular aza-Wittig reaction involving a lactam carbonyl group that delivered the diazepine core unit was the key step in the synthesis.